The Influence of e-Servqual and Financial Compensation on Driver Loyalty with Satisfaction as a Mediator - Ahdiyana Pamungkas, Benni; Hadi Pranata, Cristian (Journal Research of Social Science, Economics, and Management, 2025)
Driver loyalty, as a crucial stakeholder component in the ride-hailing industry, plays a vital role in ensuring business continuity. This study aims to examine the effect of driver satisfaction on loyalty, as well as the influence of financial compensation and e-Servqual on driver satisfaction. The research adopts a positivist paradigm and employs a hypothetical-deductive approach. A quantitative method was applied through a single cross-sectional survey involving 178 respondents, selected using non-probability and purposive sampling techniques. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that both e-Servqual and financial compensation have a significant positive effect on driver satisfaction. Additionally, satisfaction significantly influences driver loyalty. This study contributes to addressing the research gap concerning driver loyalty, which remains underexplored within the context of Indonesia’s ride-hailing industry.